2019
DOI: 10.3390/brainsci9110293
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Biochemical Alterations in Ischemic Stroke Using Fourier Transform Infrared Imaging Spectroscopy—A Preliminary Study

Abstract: Objective: Brain damage, long-term disability and death are the dreadful consequences of ischemic stroke. It causes imbalance in the biochemical constituents that distorts the brain dynamics. Understanding the sub-cellular alterations associated with the stroke will contribute to deeper molecular understanding of brain plasticity and recovery. Current routine approaches examining lipid and protein biochemical changes post stoke can be difficult. Fourier Transform Infrared (FTIR) imaging spectroscopy can play a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 73 publications
(108 reference statements)
1
9
0
Order By: Relevance
“…Previous studies suggest the decrease in FA in the chronic stage (after 3 weeks) mainly reflects chronic WM degeneration ( Jung et al, 2017 ). Recently, studies with transmission electron microscopy also found the loss of structural integrity of axons in the WM bundles right below the sensorimotor cortex ischemic lesion site in a similar animal model ( Rakib et al, 2019 ), which agrees well with the decreased FA in the ipsilesional external capsule that we found in this study.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies suggest the decrease in FA in the chronic stage (after 3 weeks) mainly reflects chronic WM degeneration ( Jung et al, 2017 ). Recently, studies with transmission electron microscopy also found the loss of structural integrity of axons in the WM bundles right below the sensorimotor cortex ischemic lesion site in a similar animal model ( Rakib et al, 2019 ), which agrees well with the decreased FA in the ipsilesional external capsule that we found in this study.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, it is known that free radicals mainly react with carbon double bond sites present in unsaturated lipids, resulting in carbonyl compound formation and lipid chain fragmentation [ 30 , 31 , 32 , 33 ]. Therefore, the high expression of C=O groups is related to the stable end-products of lipid peroxidation and, in consequence, the analyses of lipid oxidation status, measuring C=O/CH 2 content by μFTIR, have been performed in different studies [ 15 , 27 , 34 ]. Taking these data into account, our observations suggest that the lipids in GM could be more oxidized than in WM.…”
Section: Discussionmentioning
confidence: 99%
“…A FTIR micro-spectrometer (Agilent Cary 620, Cary, NC, USA) was used to record the FTIR spectra and maps within the range of 4000-700 cm −1 (spectral resolution 4 cm −1 ). More detailed instrument configurations and parameters used for this study were conducted as in our previous studies [15,16,25,41,42]. The FTIR spectra from two identical anatomical brain regions in the cortex and corpus callosum of different animals from each group were extracted from the FTIR images.…”
Section: Fourier Transform Infrared Imaging (Ftir) Studymentioning
confidence: 99%
“…Lipid molecular and structural alterations, lipid/protein band ratios (that provide facts about the protein-lipid asymmetry and environmental changes, which lead to devastating effect on the cellular function), vector normalization, and second derivatives of raw spectra were used and calculated according to the details explained in our previous studies [15]. Relative quantification of the protein content and the distribution of amide I components were determined according to our previous studies [15,16,25,41,42]. The mean was generated for each animal group along with their standard deviation (significant level p < 0.0001).…”
Section: Fourier Transform Infrared Imaging (Ftir) Studymentioning
confidence: 99%
See 1 more Smart Citation